In Vitro and In Vivo Activities of LB 10827, a New Oral Cephalosporin, against Respiratory Pathogens - Paek, Kyong-Sook (American Society for Microbiology, 2000)
The in vitro antibacterial activities of LB 10827, a new oral cephalosporin, against common respiratory tract pathogens were compared with those of six β-lactams (cefdinir, cefuroxime, cefprozil, penicillin G, amoxicillin-clavulanate, and ampicillin), two quinolones (trovafloxacin and ciprofloxacin), and one macrolide (clarithromycin). The MIC of LB 10827 at which 90% of the penicillin-resistant strains of Streptococcus pneumoniae tested were inhibited was 0.5 μg/ml, and the drug was 4- to 32-fold more active than the compared β-lactams. The potent activity of LB 10827 against Haemophilus influenzae and Moraxella catarrhalis was retained, and the presence of β-lactamase in both strains had little effect on the in vitro activity of the compound. Time-kill studies revealed that LB 10827 had bactericidal activity against these respiratory pathogens. This agent reduced original counts of all pathogens tested by ≥3 log(10) CFU/ml at the MIC, and the regrowth was completely prevented for 12 h. The potent in vitro antibacterial activity of LB 10827 against respiratory pathogens has been proved in both mouse pneumonia and neutropenic rat models. These results strongly suggest that this agent has potential for the treatment of respiratory tract infections.